THE IMPACT OF TECHNOLOGY INTEGRATION ON STUDENT ENGAGEMENT AND ACHIEVEMENT - Dinar Ayu Mirunggan Sari (Education Studies and Teaching Journal (EDUTECH), 2024)
Integration AI-driven adaptive learning systems has the potential to address the challenges of student engagement and achievement in primary education, especially in contexts of socio-economic inequality. This research aims to explore the impact of this technology through systematic literature review using the PRISMA framework. The results show that technologistsAI-based adaptive technology significantly increases student engagement and academic achievement, with the potential to reduce social inequality. The implications of this research include recommendations for educators and policy makers to maximize access and effectiveness of technology in basic education globally.